The Influence of Leadership and School's Committees on the Quality of Learning - Gunawan, Wahyu; Fitria, Happy; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to determine whether there is an influence of the leadership of the principal and the school’s committee on the quality of learning. This research was conducted at SD Negeri Cluster 1 in Sungaiselan District. The type of this research is quantitative. The sample in this study was a teacher at SD Negeri Cluster 1 in Sungaiselan District, totaling 54 people. The technique used in this study is a questionnaire. The results of the study concluded that (1) there was a significant influence on the leadership of the principal on the quality of learning. Based on the significance test, the value of t count is 2,476 > t value of table 2.004, then Ha is accepted. (2) There is a significant influence on the school’s committee on the quality of learning. Based on the significance test, the value of t count 7,115> t value of table 2.004, then Ha is accepted. (3) There is a significant influence together with the leadership of the principal and school’s committee on the quality of learning. Based on the results of the ANOVA test, an F-count of 1754,085 was obtained with a significant level of 0,000, then f count > F-table (1754,085 > 2.78) so H0 was rejected. If H0 is rejected, the conclusion is that there is an influence between independent variables simultaneously on the dependent variable.